Theoretical Analysis on the Economic Performance of Micro Gas Turbine-Trigeneration System with Different Operation Strategies for Residential Building in a Tropical Region - F., Basrawi; M. R. R., Chand; K. H., Koo; Ibrahim, Thamir K. (EDP Sciences, 2016)
This study investigates how operation strategies of micro gas turbine trigeneration system (MGTTGS) affect its economic performance. MGT-TGS was required to sustain power, heating and cooling load of 148 residential terrace houses located in Kuala Lumpur. Based on the load requirement, there were two sizes of MGTs adopted in the research scope, a 30kW and 60kW respectively. Four typical operation strategies; powermatch, heat-match, mix-match, and base-load were investigated. Life cycle cost analyses with Net Present Value as the indicator were carried out. It was found that MGT-TGS can only generate positive NPV within 25 years of life time under unsubsidized electricity price. In addition, only mix-match and power-match operation strategies offered positive NPV. Under the scheme of the latter operation strategies, the MGT achieved power generation efficiency ranging from 27% to 28% respectively due to higher partial load ratio. Furthermore, these operation strategies generated excess electricity that consequently increased the profit from electricity saving. Economically, there were less capital cost, operation and maintenances (O&M) cost and replacement cost on operating the system under the mixed match scheme and power match scheme. However Net Present Value analysis indicated that the mixed match strategies offer better economic performances than power match strategies and other operation strategies for the MGT-TGS.